Simple Hydrothermal Synthesis of Ultra-Small Cerium Oxide Nanoparticles - Wee, Boon Siong; Syazani Azaim, Eddie Halim; Choo, Thye Foo (Springer Nature, 2024)
Cerium oxide, CeO2 nanoparticles (NPs) have been synthesized through various methods to achieve the desired physicochemical properties. However, high temperatures, pressure and long reaction time were involved. In this study, ultra-small CeO2 NPs were successfully synthesized using the hydrothermal method but under a favourably low temperature (70 ℃) for 4 hours using cerium nitrate hexahydrate, Ce(NO3)3 • 6 H2O and sodium hydroxide, NaOH as the precursors while deionized water was used as the solvent. The synthesized ultra-small CeO2 NPs were characterized using field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), energy dispersive X-ray (EDX), ultraviolet visible (UV-Vis) spectrometer, Fourier transform infrared (FTIR) spectroscopy, X-Ray Diffraction (XRD) and Brunauer-Emmett-Teller (BET) method. The synthesized ultra-small CeO2 NPs were determined to have an average particle size of 3.54 nm, crystallite size of 3.05 nm and a high specific surface area of 185 m2 g-1. UV-Vis spectrum also showed absorption peak at 310 nm and FTIR spectrum intense peak at 447.20 cm-1 indicating the presence of CeO2 NPs. FTIR, EDX and XRD diffraction pattern have proved that the synthesized CeO2 NPs is of high purity. This study has successfully synthesized ultra-small CeO2 NPs with optimal conditions of hydrothermal treatment at 70℃ for 4 hours and a percent yield of ~99%.